Paired Moving Charges in Mitochondrial Energy Coupling - Green, David E. (1974)
A model of mitochondrial energy coupling has been proposed based on the principles of paired charge separation and vectorial paired charge flow. The unique role of the electron transfer chain and ionophores in mediating charge separation is emphasized.